2012
DOI: 10.3748/wjg.v18.i34.4651
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between hepatic iron and lipid metabolism with possible relevance to steatohepatitis

Abstract: The liver is an important site for iron and lipid metabolism and the main site for the interactions between these two metabolic pathways. Although conflicting results have been obtained, most studies support the hypothesis that iron plays a role in hepatic lipogenesis. Iron is an integral part of some enzymes and transporters involved in lipid metabolism and, as such, may exert a direct effect on hepatic lipid load, intrahepatic metabolic pathways and hepatic lipid secretion. On the other hand, iron in its fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
84
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 98 publications
5
84
0
Order By: Relevance
“…Thus, iron accumulation in the liver may interact and alter hepatic lipid metabolism. [9,15] Previous study about alteration of cholesterol synthesis in iron overload condition showed that from various genes related to cholesterol synthesis, some genes showed unsignificant increase of expression while a gene showed negative correlation with increase of cholesterol synthesis. [14] The other study also revealed decline of both forms of 3-hydroxy 3-methylglutaryl Iron overload has corelation with lipid metabolism, however the conclusion is still debatable.…”
Section: Total Cholesterol Serummentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, iron accumulation in the liver may interact and alter hepatic lipid metabolism. [9,15] Previous study about alteration of cholesterol synthesis in iron overload condition showed that from various genes related to cholesterol synthesis, some genes showed unsignificant increase of expression while a gene showed negative correlation with increase of cholesterol synthesis. [14] The other study also revealed decline of both forms of 3-hydroxy 3-methylglutaryl Iron overload has corelation with lipid metabolism, however the conclusion is still debatable.…”
Section: Total Cholesterol Serummentioning
confidence: 99%
“…Meanwhile, other study about hepatic iron overload using carbonyl iron in the methionine-choline deficient rat model of NAFLD is associated with decreased hepatic triglyceride. [9] Another study of iron overload in humans homozygous for the Cys282-Tyr (C282Y) mutation in HFE, which causes hemochromatosis, plasma low-density lipoprotein (LDL) cholesterol has been found to be reduced. Besides, there was also negative correlation between iron overloas and upregulation of transcriptions of Abca1 and Abcb4 which related to cholesterol export to the plasma.…”
Section: Total Cholesterol Serummentioning
confidence: 99%
See 3 more Smart Citations